OPTIMIZING THE DR-SUBMODULAR FUNCTION ON THE INTEGER LATTICE TO MAXIMIZE THE INFLUENCE OF VIRAL MARKETING ON COMMUNITIES - Nguyen Thi Bich Ngan; Nguyen Truong Phat; Do The Sang; Pham Nguyen Huy Phuong (HUIT Journal of Science, 2025)
As society continues to develop, individuals encounter increasingly complex optimization problems with multiple objectives to achieve. One such problem is optimizing a DR-submodular function, characterized by diminishing returns. In this article, we focus on maximizing the influence of marketing spread on social network communities, using a novel technique known as streaming data browsing. Our proposed DR-SubOptStream algorithm yields positive results, achieving an acceptable approximation of the objective function value and better complexity than existing algorithms. To conduct experiments, we transform social network data from a connected graph form to bipartite data form and then run the algorithm on preprocessed datasets. Overall, our findings demonstrate the effectiveness of our approach in solving this type of problem.